2021
DOI: 10.1021/acsearthspacechem.0c00250
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Induced Processing of Methanol Ice

Abstract: The formation of methane (CH4), formaldehyde (H2CO), ethylene glycol (HOCH2CH2OH), methoxymethanol (CH3OCH2OH), dimethyl ether (CH3OCH3), and ethanol (CH3CH2OH) upon electron irradiation of condensed multilayer adsorbates of CH3OH as a model of cosmic CH3OH ice has been monitored by the combined use of electron-stimulated and thermal desorption experiments. The energy-dependent relative yields of all products were measured between 2.5 and 20 eV, and the reaction mechanisms of product formation were deduced. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 72 publications
(276 reference statements)
2
26
0
Order By: Relevance
“…Spectra have been offset vertically for clarity and methane (CH 4 ). The formation of these products is in line with the results reported by prior studies of electron irradiation of frozen CH 3 OH [8,15,[19][20][21][22].…”
Section: High-energy Electron Irradiation Of Amorphous Ch 3 Oh Icesupporting
confidence: 89%
See 2 more Smart Citations
“…Spectra have been offset vertically for clarity and methane (CH 4 ). The formation of these products is in line with the results reported by prior studies of electron irradiation of frozen CH 3 OH [8,15,[19][20][21][22].…”
Section: High-energy Electron Irradiation Of Amorphous Ch 3 Oh Icesupporting
confidence: 89%
“…Increases in the 160 K spectrum at wavenumbers <1000 cm −1 are due to changes in the high-temperature background profile that are not taken into account by the background spectrum measured at 20 K concentration of this molecule within the ice structure (Figs. 5 and ν1, ν3 H2O 14.00 [37] ment with the findings of several other studies considering the electron irradiation of CH 3 OH, such as those by Bennett et al [21] and Schmidt et al [22]. Our thermal processing of a mixed H 2 O:SO 2 ice of compositional ratio 3:5 demonstrated that as the ice mixture was warmed from 20 K, molecular reactions resulted in the formation of new products, namely HSO − 3 and S 2 O 2− 5 .…”
Section: Thermal Chemistry In a Mixed Ice Containing H 2 O And Sosupporting
confidence: 75%
See 1 more Smart Citation
“…While this ionization-driven reaction mechanism is temptingly simple, a deeper insight into the reactions occurring in the ice mixtures is of utmost importance to arrive at a comprehensive understanding of the electron-induced chemistry in ices. The potential complexity of the reaction networks is obvious considering the wealth of products that can be formed even in a pure ice as exemplified by the case of pure methanol (CH 3 OH) ice [15,20]. As another example, ethanol (C 2 H 5 OH) formation was also observed as consequence of electron attachment (EA) to C 2 H 4 in the presence of H 2 O [18] indicating that different reaction mechanisms can contribute to the formation of a particular product.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to unravel electron-induced chemistry in ices, we have recently conducted comprehensive studies by post-irradiation thermal desorption spectrometry (TDS) on thin layers of different pure and mixed ices [20][21][22][23]. In each case, the dependence of product formation on electron energy was monitored for several products.…”
Section: Introductionmentioning
confidence: 99%